Co-microencapsulation of Lactobacillus plantarum and DHA fatty acid in alginate-pectin-gelatin biocomposites. (1st November 2018) - Vaziri, Asma Sadat; Alemzadeh, Iran; Vossoughi, Manouchehr; Khorasani, Alireza Chackoshian
Highlights: Probiotic and DHA were co-encapsulated using alginate-pectin-gelatin biocomposites. Pectin and gelatin improved gastrointestinal-resistant behavior of alginate beads. Optimization of biocomposite composition was done by using simplex-lattice design. High encapsulation efficiency of probiotic and DHA fatty acid was achieved. Abstract: The aim of this study was to investigate the co-microencapsulation of Lactobacillus plantarum and DHA-rich oil in a novel gastrointestinal-resistant biocomposite composed of alginate, pectin and gelatin. The optimal biocomposite consisted of 1.06% alginate, 0.55% pectin and 0.39% gelatin showed 88.66% survivability of the microencapsulated cells compared to the free cells (50.36%). In addition, co-microencapsule containing probiotic and DHA fatty acid was synthesized and physicochemically analyzed using SEM, FTIR, TGA, XRD. The results from SEM clearly confirmed that cells were completely entrapped in the matrix and DHA increased smoothness and compactness of the surface of the particles. FTIR spectra revealed the formation of hydrogen and Van der Waals bonds between macromolecules and the core materials. X-ray pattern of co-microencapsules identified amorphous structure compared to capsules containing only DHA or probiotic. TGA analysis revealed the thermal stability of DHA-loaded capsules compared to un-loaded ones.